Synergistic killing of lung cancer cells by cisplatin and radiation via autophagy and apoptosis - LIU, MIN (D.A. Spandidos, 2014)
Cisplatin is a commonly used drug for chemotherapy, however, whether it may be used synergistically with radiotherapy remains unclear. The present study investigated the underlying mechanisms of synergistic killing by radiosensitization and cisplatin, with a focus on the growth inhibition, apoptosis and autophagy of non-small cell human lung cancer cells in vitro and in a tumor xenograft in vivo. A549 cells were used for the in vitro experiments and divided into the following four treatment groups: Sham-irradiated; conventional radiotherapy (CRT) of five doses of 2 Gy every day; hyperfractionated radiotherapy of five doses of 2 Gy (1 Gy twice a day at 4 h intervals) every day; and CRT plus cisplatin. A xenograft tumor-bearing C57BL/6 model was established for the in vivo experiments and the above-mentioned treatments were administered. MTT and colony formation assays were used to detect cell viability and western blotting was performed to detect the levels of protein expression. Monodansylcadaverine staining and the immunofluorescence technique were used to analyze the autophagy rate, while flow cytometry and immunohistochemistry were performed to detect the expression levels of the genes associated with apoptosis and autophagy, including microtubule-associated protein 1 light chain 3 (MAPLC3)-II, phosphoinositide 3-kinase (PI3K) III, Beclin1, phosphorylated protein kinase B (p-AKT), damage-regulated autophagy modulator (DRAM), B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X protein, caspase-3 and p21. The MTT assay demonstrated that cisplatin exhibits a dose-dependent cytotoxicity in A549 cells and synergizes with radiation to promote the cell-killing effect of radiation. In the xenograft mouse model of Lewis cells, cisplatin plus ionizing radiation (IR) (five doses of 2 Gy) yielded the most significant tumor suppression. The autophagic vacuoles, the ratio of MAPLC3-II to MAPLC3-I (LC3-II/LC3-I) and the levels of Beclin1 were found to increase in all treatment groups, with the most marked upregulation observed in the CRT plus cisplatin treatment group. In addition, caspase-3 processing was enhanced in the group treated with the combination of cisplatin with radiation, compared with the group treated with radiation alone. Fractionated IR resulted in a significant increase in p21 expression, which was further enhanced when combined with cisplatin. Furthermore, treatment with cisplatin and fractionated IR resulted in a significant elevation of the expression of the autophagy-related genes, PI3KIII, Beclin1 and DRAM1. However, the levels of p-AKT were observed to decline following exposure to fractionated IR in the presence or absence of cisplatin. As for the apoptosis signaling genes, the combination of cisplatin and fractionated IR therapy resulted in a significant decrease in Bcl-2 expression and a marked upregulation of p21 expression. The current study offers strong evidence that the combination of cisplatin with radiation strengthens the killing effect of radiation via pro-apoptotic and pro-autophagic cell death.